New laboratory tests for evaluating the effectiveness of the method of transosseous osteosynthesis for treatment of patients with chronic osteomyelitis of the foot bones - Maksim V. Stogov; Anatolii S. Sudnitsyn; Elena A. Kireeva; Nikolai M. Kliushin (Гений oртопедии, 2022)
Introduction The use of laboratory tests to monitor the treatment of patients with chronic osteomyelitis has a lot of clinical relevance. The purpose of the study was to identify laboratory tests for assessing metabolic processes in patients with purulent lesions of the foot bones for monitoring the dynamics of the recovery processes in the course of treatment. Methods The studies were carried out in 36 patients with chronic osteomyelitis of the calcaneus and adjacent bones of the foot of traumatic etiology. All patients were treated with the method of the Ilizarov transosseous osteosynthesis. Biochemical and coagulation parameters were studied. Results It was found that in patients with purulent lesions of the foot bones, the elevated levels of blood serum lactate were most frequently detected before surgery (52.8 %, 95 % CI: 36.6-68.6). The incidence of elevated CRP was 27.7 % (95 % CI: 14.6-43.3) on average, and one third of patients had elevated fibrinogen levels (33.3 %, 95-CI: 19.1-49, 3). During the treatment period, the incidence of elevated lactate levels in patients did not change but the incidence of elevated CRP levels increased significantly which was observed in 77.8 % of patients on the 3rd post-surgery day. By discharge from the hospital, elevated values of CRP and lactate occurred in 11.1 % of patients. It is assumed that the greatest diagnostic significance is the assessment of the level of lactate in the dynamics of the treatment in target patients. Discussion Based on the results of the studies, a laboratory sign was found that indicates the effectiveness of surgical treatment in patients with chronic osteomyelitis of the foot bones using the method of transosseous osteosynthesis. Such a sign is a decrease in the initially elevated concentration of lactate in the blood serum of patients in the postoperative period. The detected sign meets the requirements for its applicability in laboratory tests: 1) this sign is the most common in the target group of patients; 2) the dynamics of changes in the level of lactate correlates with the ongoing treatment; 3) this test is an indicator of a significant physiological process: oxidative metabolic processes in patients with the studied pathology.